275 Prevalence of uterine sarcomas in the oncological gynecology unit of the san borja arriaran hospital. (13th November 2020) - Cervantes, P; Altamirano, R; Nazzal, O; Castillo, C; Solari, M; Pincheira, E; Rojas, J; Suarez, E
Abstract : Introduction: Uterine sarcomas are relatively rare, between 3 and 8% of uterine cancers. The most common tumors are leiomyosarcomas (LMS) (59%) and endometrial stromal sarcomas (ESS) (33%). Material and Method: Retrospective review from January 2014 to February 2020. Patients diagnosed with carcinosarcoma were excluded. The global survival (GS) was taken from the diagnosis of the disease to the death of the patient or last control. Figo 2009 was used for staging. Results: A total of 295 patients with uterine cancers with a median age of 59. 16 patients had uterine sarcoma, from which 44% were LMS (7), 13% low-grade ESS (2) and 44% high grade ESS (7). 94% underwent standard treatment. The LMS FIGO IB 43% (3), with GS median of 17 months; FIGO IIIC 14% (1), with GS 15 months; and FIGO IV 43% (3) with GS median of 23.6. 100% low-grade ESS (2) FIGO IB with GS median of 51 months, and 100% high-grade ESS (7) FIGO IB with GS median of 28. In 43% (3) of the high-grade ESS recurrence appeared between 3 to 16 months with a median of 11 months (2 to the lung and 1 to the abdominal cavity), and 50% of low-grade ESS at 60 months. A prevalence of uterine sarcomas of 5.4% was found. Conclusion: Uterine sarcomas represented 5% of the primary uterine neoplasms. In our review the highest percentage (61%) were ESS and not LMS. Low-grade ESS are rare compared to other sarcomas and have higher GS.